2000
DOI: 10.1042/bj3500805
|View full text |Cite
|
Sign up to set email alerts
|

Identification of transient glycosylation alterations of sialylated mucin oligosaccharides during infection by the rat intestinal parasite Nippostrongylus brasiliensis

Abstract: The sialylation of the oligosaccharides from small-intestinal mucins during a 13-day infectious cycle was studied in Sprague-Dawley rats with the parasite Nippostrongylus brasiliensis. Sialic acid analysis and release, permethylation and analysis by GC-MS of the sialylated oligosaccharides isolated from the 'insoluble' mucin complex revealed a relative decrease (4-7-fold) of N-glycolylneuraminic acid compared with N-acetylneuraminic acid just before parasite expulsion. Northern blots showed that this effect wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…Mucosal scrapings from Sprague-Dawley rats were collected at different stages of the infection, and the insoluble mucin complex (5) was isolated after repeated extraction with guanidinium chloride. As described before, the amount of collected insoluble mucins increased up to day 12-13 and then quickly reverted to normal after parasite expulsion (18).…”
Section: The Effect Of the N Brasiliensis Infection On The Expressiosupporting
confidence: 73%
See 2 more Smart Citations
“…Mucosal scrapings from Sprague-Dawley rats were collected at different stages of the infection, and the insoluble mucin complex (5) was isolated after repeated extraction with guanidinium chloride. As described before, the amount of collected insoluble mucins increased up to day 12-13 and then quickly reverted to normal after parasite expulsion (18).…”
Section: The Effect Of the N Brasiliensis Infection On The Expressiosupporting
confidence: 73%
“…In a previous study we reported glycosylation alterations among sialylated oligosaccharides on the rat Muc2 mucin during N. brasiliensis infection (18). Detailed structural characterization of sialylated Muc2 oligosaccharides prepared from small intestinal mucosal scrapings of infected rats at different stages of the infection revealed two events of altered glycosylation.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…spiralis , T. muris and H . polygyrus 76, 77, 78, 79. It has yet to be determined whether these changes occur as a result of the inflammatory environment or to resolve the infection; clearly more research is required to define the precise role of mucin glycans.…”
Section: Gi Nematode Infection and Alterations In Mucin Glycomementioning
confidence: 99%
“…Although the chemical alterations of colonic mucins in response to E. histolytica have not been addressed, changes in the glycosylation patterns of rat mucin have been observed during Nippostrongylus brasiliensis infection (77). These transient alterations in sialylated oligosaccharides have been directly related to parasite expulsion.…”
Section: Mucinmentioning
confidence: 99%